Could Metabolic Syndrome Be a Predictor of Survival Outcomes in Upper Tract Urothelial Carcinoma? A Propensity Score Matching Study in a Large Chinese Center - Dai, Xiang; Wang, Fei; Du, Yiqing; Qin, Caipeng; Lai, Shicong; Song, Yuxuan; Huang, Zixiong; Han, Songchen; Zhang, Xiaopeng; Xu, Tao (Frontiers in Oncology, 2022)
Purpose: To evaluate the prognostic value of metabolic syndrome (MetS) based on propensity score matching (PSM) analysis. Patients and methods: A total of 573 patients with UTUC after radical nephroureterectomy were included at Peking University People’s Hospital from January 2007 to April 2021. MetS was diagnosed according to the criteria of Chinese Diabetes Society (CDS) in 2019, and was defined as the presence of 3 or more of the following 4 conditions (obesity, hyperglycemia, hypertension, high triglycerides and/or low high-density lipoprotein-cholesterol). Univariate and multivariate Cox regression analysis were used to evaluate the association of MetS and its components with pathological outcomes after adjusting preoperative confounders by propensity score matching. All patient variables were adjusted using 1:1 PSM analysis with a caliber of 0.02 to minimize selection bias. Kaplan-Meier method was used to estimate OS, CSS and IVRFS after surgery. Results: MetS was significantly correlated with older age, a history of coronary heart disease, high Charlson Comorbidity Index, low estimated Glomerular filtration rate and low AST/ALT ratio (all P<0.05). Multivariate cox regression analysis and Kaplan-Meier curves demonstrated that MetS showed no statistical correlation with lower OS and IVRFS, and a borderline negative correlation with lower CSS (P=0.063) than those without MetS before PSM. After PSM, the 5-year OS, CSS, and IVRFS were 64.1%, 74.7%, and 77.2% in the MetS group, as compared with 67.4%, 78.8%, and 77.2% in non-MetS group. Univariate Cox regression analyses showed that MetS and its components were not associated with decreased OS, CSS, or IVRFS (all P>0.05). Conclusion: In our study, no statistical difference was found between MetS and survival outcomes in UTUC, except a borderline correlation with lower CSS. Further studies are demanded to evaluate the role of MetS and its each single components on UTUC.